Freestyle arm entry effects on shoulder stress, force generation, and arm synchronisation - Becker, T.; Havriluk, R. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
A previous study showed that immediately after the arm entry, female butterfly swimmers were not efficient in 30% of the stroke cycle because their arms were in a biomechanically disadvantageous position (Becker & Havriluk 2010). The swimmers completed their arm entry with their hands closer to the surface than their shoulders in a position that stressed their shoulders. They generated minimal force until the hands submerged below the level of the shoulders. In a subsequent study on male and female freestyle swimmers (Havriluk & Becker 2011), over half of the swimmers (mostly females) completed the arm entry with their hand closer to the surface than their shoulder in a stressful position similar to butterfly. Given the prevalence of shoulder injuries from butterfly and freestyle (e.g. Hupenthal2006; Rodeo 2011), further examination of the arm entry is appropriate. The present study was designed to determine the prevalence of an ineffective arm entry in freestyle and the impact on shoulder stress and force generation. Because of the wasted time from an ineffective arm entry position, the effect on arm synchronisation was also calculated. Due to the previously found gender difference in arm entry, the variables were stratified by gender.